Tabun-inhibited rat tissue and blood cholinesterases and their reactivation with the combination of trimedoxime and HI-6 in vivo - Bajgar, Jiri; Karasova, Jana Zdarova; Kassa, Jiri; Cabal, Jiri; Fusek, Josef; Blaha, Vaclav; Tesarova, Sandra (Chemico-biological interactions, 2010)
Up to now, intensive attempts to synthesize a universal reactivator able to reactivate cholinesterases inhibited by all types of nerve agents/organophosphates were not successful. Therefore, another approach using a combination of two reactivators differently reactivating enzyme was used: in rats poisoned with tabun and treated with combination of atropine (fixed dose) and different doses of trimedoxime and HI-6, changes of acetylcholinesterase activities (blood, diaphragm and different parts of the brain) were studied. An increase of AChE activity was observed following trimedoxime treatment depending on its dose; HI-6 had very low effect. Combination of both oximes showed potentiation of their reactivation efficacy; this potentiation was expressed for peripheral AChE (blood, diaphragm) and some parts of the brain (pontomedullar area, frontal cortex); AChE in the basal ganglia was relatively resistant. These observations suggest that the action of combination of oximes in vivo is different from that observed in vitro.
Keywords: aktivace enzymů; Animals; Acetylcholinesterase; Female; potkani Wistar; Rats, Wistar; Enzyme Activation; ženské pohlaví; oximy; otrava organofosfáty; Pyridinium Compounds; pyridinové sloučeniny; trimedoxim; Organophosphates; Central Nervous System; Oximes; Trimedoxime; acetylcholinesterasa; organofosfáty; reaktivátory cholinesterasy; kombinovaná farmakoterapie; krysa rodu Rattus; zvířata; centrální nervový systém; Organophosphate Poisoning; Rats; Cholinesterase Reactivators; Drug Therapy, Combination